Infected Baerveldt Glaucoma Drainage Device by Aspergillus niger - Nurul-Laila Salim; Yaakub Azhany; Zaidah Abdul Rahman; Roziawati Yusof; Ahmad Tajudin Liza-Sharmini (Case Reports in Ophthalmological Medicine)
Fungal endophthalmitis is rare but may complicate glaucoma drainage device surgery. Management is challenging as the symptoms and signs may be subtle at initial presentation and the visual prognosis is usually poor due to its resistant nature to treatment. At present there is lesser experience with intravitreal injection of voriconazole as compared to Amphotericin B. We present a case of successfully treated Aspergillus endophthalmitis following Baerveldt glaucoma drainage device implantation with intravitreal and topical voriconazole.